Nationwide population-based cohort study to assess risk of surgery for adhesive small bowel obstruction following open or laparoscopic rectal cancer resection. Issue 2 (26th July 2017) - Andersen, P; Jensen, K K; Erichsen, R; Frøslev, T; Krarup, P-M; Madsen, M R; Laurberg, S; Iversen, L H
Abstract: Background: Laparoscopic surgery has been reported to reduce the formation of adhesions following colorectal surgery. The aim of this nationwide cohort study was to investigate the risk of surgery for adhesive small bowel obstruction (SBO) following open and laparoscopic rectal cancer resection. Methods: Patients undergoing rectal cancer resection between 2005 and 2013 were identified in the Danish Colorectal Cancer Group database. The primary outcome of surgery for adhesive SBO was identified in the Danish National Patient Registry. The risk of surgery for adhesive SBO was estimated as the cumulative incidence proportion, treating death as a competing risk. Cox proportional hazards regression analysis with multivariable adjustment was used to compute hazard ratios (HRs). The secondary outcome was 30-day mortality after surgery for adhesive SBO. Results: Of 7657 patients, 340 (4·4 per cent) underwent surgery for adhesive SBO. The 5-year risk of surgery for adhesive SBO was 4·5 per cent among 4472 patients undergoing open resection and 3·0 per cent among 3185 patients having a laparoscopic resection. Laparoscopic rectal resection was associated with a lower risk of subsequent operation for adhesive SBO (adjusted HR 0·65, 95 per cent c.i. 0·50 to 0·86; P = 0·002). The adjusted HR of mortality after adhesive SBO was 0·84 (0·37 to 1·91; P = 0·671) comparing patients with previous laparoscopic and open resection. Conclusion: Laparoscopic rectal cancer resection was associated with a decreased risk of surgery for adhesive SBO. There was a substantial difference in 30-day mortality after surgery for adhesive SBO based on the surgical approach used at the time of rectal resection. Graphical Abstract: Laparoscopic rectal cancer resection was associated with a decreased risk of surgery for adhesive small bowel obstruction. No substantial difference in 30-day mortality after surgery for adhesive small bowel obstruction according to surgical approach at rectal resection was observed. Laparoscopic approach is better